Teaching Arabic oral and written communication among the Yoruba speakers in Nigeria: A constrastive analysis - Olatunde Yaqub, Muhammad (Issues in Language Studies, 2014)
The teaching and learning of Arabic language especially in the non-native environment require a simplified method to make the job a more fruitful enterprise. This paper explores the application of a contrastive analysis of both the target language and the native language in encouraging, motivating and simplifying the teaching and learning of oral Arabic communication skill among the native Yoruba speakers. The work identifies the major areas of difficulties facing the students from this region. This includes phonetics, phonology and agreement relation (otherwise known as concord in grammar). The agreement consists of gender, person, terms and numbers which form a major component of grammatical Arabic sentence. It is observed that understanding these major areas will enhance the performance of the students in achieving the required standard in Arabic oral communication. The paper concludes that Arabic phonetics, phonology and grammar are more elaborate than those of Yoruba. Hence, the instructors need to focus more attention on these difficult areas; especially those areas that do not exist in the native language (Yoruba).